FAKTOR-FAKTOR YANG MEMPENGARUHI JUMLAH PENGUNJUNG KE OBJEK EKOWISATA PANTAI SIURI, DESA TOINASA KECAMATAN PAMONA BARAT KABUPATEN POSO - Modjanggo, Frits; Sudhartono, Arief; Sustri, Sustri (Universitas Tadulako, 2015)
Central Sulawesi Province has enough varied landscapes with very attractive natural richness and high enough biodiversity potency. This region has a high chance to be developed in the future on its opportunities on the ecotourism development that one of them is Siuri beach. This research was conducted at the coastal tourtism object of Siuri beach, Toinasa Village - West Pamona District - Poso Regency as long as three months from May to July 2013. This research aims are: (a) knowing the motivation of visitors to the ecotourism object of Siuri beach and (b) determining affecting factors on the number of visitors to the ecotourism object of Siuri beach used descriptive and correlation analysis methods. Descriptive method was used to analyze respondents motivation by explaining in detail what drives them to come to the ecotourism object location of Siuri beach. While the correlation analysis methods was used to analyze affecting factors on the number of visitors to the ecotourism object of Siuri beach.The research results shown that the visitors motivation to come to the ecotourism object location of Siuri beach consist of: achievemental motivation, individual motivation, and physical motivation. While the results of correlation analysis shown that factors of age, education, revenue, facilities, manager service, promotion and security related significantly to the number of visit, but only the distance is not significantly related to the number of visit. The magnitude of the relationship (correlation) among of the all factors simultaneously on the number of visit was calculated by correlation coeffisient (R) that is 0.363. This indicate that those all factors (age, education, revenue, facilities, manager services, promotion, and security) have a low impact on the number of visitors. Keywords: correlation, ecotourism,motivation, Siuri beach, visitors